Public–private partnerships in Tanzanian affordable housing schemes: Policy and regulatory issues, pitfalls and solutions. Issue 2 (4th December 2018) - Kavishe, Neema; Chileshe, Nicholas; Jefferson, Ian
Abstract : Purpose: The purpose of this paper is to identify and rank policy and regulatory framework factors and inherent pitfalls in the delivery of Tanzanian public–private partnerships (PPPs) affordable housing schemes. The strength of interactions between pitfalls is established, with practical solution proposals offered. Design/methodology/approach: Primary data were collected from questionnaires administered to 28 Tanzanian stakeholders. Semi-structured interviews with public and private sector respondents then complemented survey findings with proposed solutions. The quantitative data were analysed using descriptive statistics, mean scores, parametric tests and correlation analyses. Directed content analysis was used for the interview transcripts. Findings: Results show that "current PPP policy and guidelines need further improvement" and "Tanzania has a PPP policy and clear regulatory framework" were rated higher as policy and regulatory factors. In contrast, "poor planning skills and analytical capacity", "high cost of building materials" and "inadequate access to housing finance" were the critical pitfalls. Most practical solutions were broadly financial in nature, or related to training, project management or PPP-enabling environment. Originality/value: The paper provides solutions that can be tailored to international practitioners interested in understanding the effects of PPP policy, regulatory issues and pitfalls on Sub-Saharan Africa and other similar developing economies.